Au3-Decorated graphene as a sensing platform for O2 adsorption and desorption kinetics. Issue 34 (18th August 2022) - Libeert, Guillaume; Murugesan, Ramasamy; Guba, Márton; Keijers, Wout; Collienne, Simon; Raes, Bart; Brems, Steven; De Gendt, Stefan; Silhanek, Alejandro V.; Höltzl, Tibor; Houssa, Michel; Van de Vondel, Joris; et al.
Abstract : A new approach to sensitively measure the sorption kinetics of molecules on few-atom clusters, by making use of a graphene sensor, is proposed. The approach is illustrated for the reaction of O2 with Au3 clusters. Abstract : The adsorption and desorption kinetics of molecules is of significant fundamental and applied interest. In this paper, we present a new method to quantify the energy barriers for the adsorption and desorption of gas molecules on few-atom clusters, by exploiting reaction induced changes of the doping level of a graphene substrate. The method is illustrated for oxygen adsorption on Au3 clusters. The gold clusters were deposited on a graphene field effect transistor and exposed to O2 . From the change in graphene's electronic properties during adsorption, the energy barrier for the adsorption of O2 on Au3 is estimated to be 0.45 eV. Electric current pulses increase the temperature of the graphene strip in a controlled way and provide the required thermal energy for oxygen desorption. The oxygen binding energy on Au3 /graphene is found to be 1.03 eV and the activation entropy is 1.4 meV K −1 . The experimental values are compared and interpreted on the basis of density functional theory calculations of the adsorption barrier, the binding energy and the activation entropy. The large value of the activation entropy is explained by the hindering effect that the adsorbed O2 has on the fluxional motion of the Au3 cluster.